INFLUENCE ANALYSIS OF THE ATTACHMENT COORDINATES RELATING TO THE CARGO OSCILLATIONS ON THE PIPE LAYING CRANE’S BOOM - R. Y. Sukharev; V. V. Tanskiy (Вестник СибАДИ)
Introduction. The work of a crane - a pipe-laying machine in difficult ground conditions has a significant influence on the process of performing the work and the mode of the machine operation. The unevenness of the microrelief is the main reason for the fluctuations in the load, often leading to emergency situations. Therefore, engineering solutions aimed at reducing the negative impact of cargo oscillations on the boom of a crane - a pipe laying - are considered in the article. Moreover, the necessity of a new engineering solution aimed at limiting the amplitude of load oscillations on a crane arm - a pipe laying - is substantiated.Materials and methods. The mathematical model is used in the research, where the crane - pipe layer is a hinged articulated link with elastic-viscous bonds superimposed on it. Additionally, the kinematics of the links are described by the method of homogeneous coordinates; the dynamics of the links are described by a system of Lagrange Equations of the 2nd type.Results. As a result, the following dependencies are constructed: the oscillation of the load from the coordinates of the attachment of the balancing rope to the boom and the load rope, for a range of boom with angles’ range from 30 ° to 80 °. Also the influence of the coordinates of the attachment of the balancing rope to the boom and the load rope on the oscillation of the load is determined for a fixed value of the length of the cargo rope.Discussion and conclusion. The estimation of the effect of the coordinates of fastening the balancing rope to the boom and the cargo rope on the oscillation of the load on the boom of the crane - the pipelayer is given.